The role of national unity and politics in grounding pancasila values and religious moderation in forming national character - A. Wahab, Gusnarib; Zaifullah, Zaifullah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Indonesia's diversity, unified by Pancasila, faces challenges from extremism, highlighting the need for religious moderation across all faiths to maintain harmony, tolerance, and national unity. This study aims to determine the role of the Central Sulawesi Province Police Department in grounding Pancasila values and religious moderation in shaping the nation's character in Central Sulawesi province, To find out the factors that inhibit the grounding of Pancasila values and religious moderation in shaping the nation's character Research The research method used is a qualitative descriptive method. The author determined the informants by the purposive sampling method The data collection techniques in this study were carried out through interviews, observations and documentation. The results and discussion of this study show that the effective role of Kesbangpol in Grounding Pancasila Values and Religious Moderation in Shaping the Nation's Character can be seen in Central Sulawesi Province the implementation of policies contained in the 2021-2026 Kesbangpol Strategic Plan, showing that the policy is realized with the implementation related to the implementation of Pancasila values, political education and national insight. Of course, this can have a positive impact on religious moderation in community life to shape the nation's character. Inhibiting factors The factors that inhibit the grounding of Pancasila values and religious moderation in shaping the nation's character in Central Sulawesi Province consist of 2 factors, namely internal factors and external factors.